EFFORTS TO COUNTER FALSE REPORTS FROM THE COMMUNITY AT THE BREBES REGENCY FIRE DEPARTMENT - Hetharie, Yosie; Ainul Close, Fahmi; Suwondo, Sutiyono (Fakultas Hukum Universitas Swadaya Gunung Jati, 2024)
The importance of legal action against perpetrators who make false reports in DAMKAR Brebes Regency. The crime of forgery is a crime that contains a system of untruth or falsehood about a thing or object that appears from the outside as if it is true when, in fact, it is contrary to the truth. This description is the background of the problem in writing, namely, what is the motive of the perpetrators who make false reports in the Brebes Regency Fire Department, and how are the efforts of the Brebes Regency Fire Department to deal with the existence of false reports of fires in the Brebes Regency area. This research method uses normative judicial, legal research that is carried out using research on literature materials or secondary data. This research can be called normative research or literature research. The results of this study show that the motive is the intentionality of the perpetrator of false reports, considering the curiosity of the perpetrator because it can be searched in the search system in the form of Google and Instagram. Furthermore, the sense of ignorance from the last perpetrator and the panic from the complainant are also factors that trigger false reports. It is not uncommon for overlapping reports to become difficult for firefighters when preparing services to carry out blackouts. When unexpected disasters occur, such as snakes, things are related to electrical circuits and many more forms. Educate the local community about the importance of doing good and correct reporting so that the effectiveness, accountability, and transparency of the Brebes Regency DAMKAR are carried out. What is the power of the community service provider if it is not supported by community cooperation?